(Studi Efek Antitumor Buah Merah, Pandanus conoideus, Dalam In Vitro Dan In Vivo) - Toshiaki Nishigaki; Kunitaka Hirose; Ingrid S. Surono; Hidekazu Shigematsu (Warta Industri Hasil Pertanian, 2011)
Pandanus conoideus (Buah Merah) Is Exclusively Grown In Papua Island And Its Neghbour Areas And Indigenous People Has Been Utilizing Its Extract Oil (SBM)Thousand OfDear Years. We Have First Found Relatively High quantity Of Carotenods which Carotenoids Which Consists Of Alph-And Bet-Carotene As Well As Alpha-And Beta-Cryptoxanthin In SBM. Beta -Eryptoxanthin Is a Of SBM Has Not Been Well Examined.We Evaluated Antitumor Potentials Of SBM In Vitro And In Vivo.In The In Viro Study, Proliferation Of Human Non-Small Lung Cancer Cells.A549Were Inhibited By SBM At More Than 500 Hg/mL iN mtt Assay . The In Vivo Antitumor Activity Of SBM Was Evaluated Using SBM Demonstrated Significant Antitumor Effects In Ether Tumor Volumes Or Tumor Weights. Experiment Using Nude Mice In A549 Assay Demonstrated That Antitumor Effect Of SBM May Not Be Associated With Involvement. We Conclude That Buah Merah Has Higher Potentiasls In Prevention Of Cancers, Especially Lung Cancer.Key Words : Pandanus Conoideus, Buah Merah, Carotenoid, Beta-Cryptoxanthin, Sarcomal 180, Lewis Lung Cancer, Non-Small Lung Cancer A549.